(untitled) (Innovative professional education, 2025)
Modern innovative approaches to career guidance and career counseling in vocational (vocational and technical) education institutions are considered. It is determined that career guidance and career counseling are necessary elements of preparing young people for professional activity. The prospects for the development of career counseling are outlined, taking into account modern challenges of the labor market.